The Relation of Age, Breed and Environment on Canine Inattention and Impulsivity : Unravelling ADHD-like Behaviour in Three Dog Breed Groups - Kankare, Miro (My University, 2025)
ADHD (attention deficit hyperactivity disorder) is a complex and sometimes controversial diagnosis. Research on its causes and impacts is challenging due to its multi-factorial origins and variability in symptom presentation, but dog (Canis familiaris) may serve as beneficial model species due to their behavioral, neurochemical, and evolutionary similarities to humans. This study assessed differences in inattention and impulsivity among three dog breed groups (companion, herding, primitive dogs) and modeled the relationship of age, breed, sex, environment, and activity in the behavior of 997 dogs. Data was collected via a questionnaire-based survey by Salonen et al. (2021) and was analysed using t-tests and generalized linear models. Results indicated that 1) the primitive breed group had lower scores in inattention than companion and herding groups; 2) age significantly impacted inattention and impulsivity, with older dogs displaying lower levels of both behaviors; 3) living environment influenced behavior, especially in herding breeds, where impulsiveness was related to residence type (detached vs. terraced houses); and 4) dogs in detached houses were rated as less inattentive and impulsive than those in terraced houses. Analyses confirmed a negative relationship between age and both inattention and hyperactivity scores. These findings underscore the importance of considering biological and environmental factors when assessing ADHD-like traits in dogs. Further research should include additional breeds, environments, lifestyles, and conditions. This study highlights the potential of dogs as model species for ADHD research, offering insights into cognitive and behavioral adaptations relevant to both evolutionary biology and practical applications for human and animal well-being.

ADHD (attention deficit hyperactivity disorder) on monimutkainen ja joskus kiistanalainen diagnoosi. Tutkimus sen syistä ja vaikutuksista on haastavaa sen monitekijäisten syiden ja oireiden esiintymisen vaihtelun vuoksi, mutta koira (Canis familiaris) voi toimia hyödyllisenä mallilajina, kun halutaan ymmärtää ADHD:n syitä. Tämä johtuu koirien ja ihmisten käytöksellisistä, neurokemiallisista ja evolutiivisista yhtäläisyyksistä. Tutkimuksessa arvioitiin kolmen koiraroturyhmän (seura-, paimen- ja alkukantaiset koirat) tarkkaamattomuus- ja impulsiivisuuseroja ja mallinnettiin iän, rodun, sukupuolen, ympäristön ja aktiivisuuden suhdetta näiden käyttäytymiseen 997:n koiran muodostamasta aineistosta. Tiedot keräsivät kyselytutkimuksella Salonen ym. vuonna 2021 ja ne analysoitiin t-testeillä ja yleistetyillä lineaarisilla malleilla. Tulokset osoittavat, että 1) alkukantaisella roturyhmällä oli matalammat pisteet tarkkaamattomuudessa kuin seura- ja paimenkoiraryhmillä; 2) ikä vaikutti merkittävästi tarkkaamattomuuteen ja impulsiivisuuteen, kun vanhemmilla koirilla oli näissä käyttäytymisissä matalammat tasot; 3) elinympäristö vaikutti käyttäytymiseen erityisesti paimenroduilla, joissa impulsiivisuus liittyi asuinpaikkatyyppiin (omakotitalot vs. rivitalot); ja 4) omakotitalojen koirat arvioitiin keskittymiskykyisimmiksi ja vähemmän impulsiivisiksi kuin rivitaloissa asuvat. Analyysit vahvistivat negatiivisen suhteen iän ja sekä tarkkaamattomuuden että hyperaktiivisuuden välillä. Nämä havainnot korostavat, että biologiset ja ympäristötekijät ovat tärkeä huomioida, kun arvioitaan koirien ADHD:n kaltaisia piirteitä. Jatkotutkimuksen tulisi sisältää lisää erilaisia koirarotuja, ympäristöjä, elämäntapoja ja olosuhteita. Tämä tutkimus korostaa, että koiria on mahdollisuus käyttää mallilajeina ADHD-tutkimuksessa. Ne auttavat ymmärtämään kognitiivisia ja käyttäytymiseen liittyviä adaptaatioita, jotka ovat merkityksellisiä sekä evoluutiobiologian että ihmisten ja eläinten hyvinvoinnin käytännön sovellusten kannalta.
Keywords: dog behavior, ADHD, dog breeds, behavioral ecology, inattention, impulsivity, living environment, evolutionary psychology, koiran käyttäytyminen, ADHD, koirarodut, käyttäytymisekologia, tarkkaamattomuus, impulsiivisuus, elinympäristö, evoluutiopsykologia